Means of Improving the Management of Projects Financed by the European Union - Răzvan NISTOR; Ioana Natalia MUREŞAN (Revista de Management Comparat International)
Projects financed by the European Union generate effects on organizations that implement them, on stakeholders and on the regions in which they are implemented. Through these projects the development of regions and the achievement of the European objectives, is wanted. These projects have special characteristics that differentiate them from other projects and need an adapted type of management. An effective and efficient project management improves the effects of projects and the obtained results. The article focuses on means of improving the management of projects financed by the European Union by identifying best practices in this field and proposing solutions for the most frequent problems that occur in the implementation of these problems.